Mg-Doped high voltage LiCoO2 for high performance lithium-ion batteries - Li Pengyu; Wu Mengqiang; Wang Xun; Xu Caili (E3S Web of Conferences, 2023)
Further increasing the voltage is the most efficient means of acquisition to obtain lithium cobalt oxide with high specific capacity, but the irreversible phase transition of LiCoO2 at high voltage leads to poor electrochemical performance. In this paper, a 4.6V high voltage stable lithium cobalt oxide cathode material was achieved by simple high temperature solid-phase synthesis method doped with different contents of Mg elements. Under the condition of Mg content of 0.02, the specific capacity of discharge is 222.7 mAh/g at 0.5C, and the capacity retention rate is 93% after 50 cycles of 1C, showing good electrochemical performance.